Sistem Pendukung Keputusan Penentuan Ranking Kenaikan Gaji Staff Dan Karyawan - Poningsih, Poningsih (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Currently AMIK and STIKOM Tunas Bangsa have approximately 100 employees (staff and employees). Each employee has a different and varied salary. Every year, AMIK and STIKOM Tunas Bangsa management provide salary increases to their employees. But the number of increases is very diverse. This decision support system will later provide recommendations to management in the form of employee performance ranking. There are several factors used in this decision support system, including work period, education and performance. The method used is Multi-objective Optimization on The Base of Ratio Analysis (MOORA). Where the advantages of MOORA are having a good level of selectivity because it can determine the objectives of the conflicting criteria.